Analysis of Interaction Between Odorant Receptors and Flexible Spike of SARS CoV-2- Key to Loss of Smell - Anwar, Firoz; Altayeb, Hisham; Alhayyani, Sultan; Kumar, Vikas; Al-Abbasi, Fahad A; Ashraf, Ghulam M. (Current Neuropharmacology, 2023)
Background: The development of a vaccine for SARS-CoV-2 is primarily focused on the structure of the spike (S) protein. The heavy glycosylation of S with flexible hinges at the stalk shields from antibody attachment. Objective: This study deciphers the flexible nature of hinges responsible for binding the odorant receptor on neurons responsible for the loss of smell in COVID-19 patients. Methods: The 3D structure via EPIK in Maestro, protein docking with ligands via Maestro protein analysis tool, and molecular dynamic simulation at 30 ns run using DESMOND was prepared. Results: The data of the study strongly suggest that strong and stable bond formation results from the reaction between R:14: Trp and Phe at the residue, targeting the flexible hinges of SARS-CoV-2. The difference in the conformational structure of the S protein and its binding with the odorant receptor in COVID-19 is the prime factor for the loss of smell and taste in patients, as supported by the concept of Antigen (epitope) Antibody interaction by the stable formation of a hydrogen bond among odorant receptor and the S protein. The flexibility of structural proteins determines the binding potential of antibodies or other defense proteins produced to participate in the antigen-antibody reaction. Conclusion: Molecular and atomic details potentiate the design and screening of small molecules that can inhibit the fusion at entry level or odorant receptors and potentially be used in the prevention and treatment of infection, particularly when formulated as nasal drops, paving a new approach for pharmacologists in the treatment of COVID-19 infection.
Keywords: spike protein